2020
DOI: 10.1186/s12913-020-05470-5
|View full text |Cite
|
Sign up to set email alerts
|

Community-based adherence clubs for postpartum women on antiretroviral therapy (ART) in Cape Town, South Africa: a pilot study

Abstract: Background With an increasing number of countries implementing Option B+ guidelines of lifelong antiretroviral therapy (ART) for all pregnant and breastfeeding women, there is urgent need to identify effective approaches for retaining this growing and highly vulnerable population in ART care. Methods Newly postpartum, breastfeeding women who initiated ART in pregnancy and met eligibility criteria were enrolled, and offered the choice of two options for postpartum ART ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…We took the approach of considering the costs for the mother-infant pair with the trialled models of care specifically assessing maternal (and infant) outcomes. In the PACER and MCH-ART studies, Model III was found to be the most effective in terms of retention of mother-infant pairs and maternal viral suppression at 12 months postpartum with 84% of mother-infant pairs meeting these criteria [18][19][20][21]; Model I had a 56%; and Model II had a 77% proportion [18][19][20]. As the population of adults living with HIV is not homogeneous, there is a need to consider having a combination of different models depending on the characteristics of the population or individual's phase of life.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We took the approach of considering the costs for the mother-infant pair with the trialled models of care specifically assessing maternal (and infant) outcomes. In the PACER and MCH-ART studies, Model III was found to be the most effective in terms of retention of mother-infant pairs and maternal viral suppression at 12 months postpartum with 84% of mother-infant pairs meeting these criteria [18][19][20][21]; Model I had a 56%; and Model II had a 77% proportion [18][19][20]. As the population of adults living with HIV is not homogeneous, there is a need to consider having a combination of different models depending on the characteristics of the population or individual's phase of life.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, not all patients will be eligible for CACs and may be better suited to care under Model I or II. CAC inclusion criteria being that patients should be adults, who have been on ART for 6‐12 months, be stable with a suppressed viral load, not be pregnant and should not require frequent clinical management for adherence issues or comorbidities [21]. For those eligible and attending a CAC, the less frequent visit requirement of CACs (see Table 1) and ability to send a treatment ‘buddy’ to collect ART may aid WLH who are working or who would be unable to come to the clinic as regularly [40].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations